Assessing soil quality using mesofauna as a potential bio-indicator: A case study in Manthali Municipality, Nepal - Tuladhar, Sarana; Lamsal, Bishal; Gurung, Smriti; Raut, Nani (Nepal Journal of Environmental Science, 2026)
Soil mesofauna is a key component of the terrestrial ecosystem that contributes to diverse soil and other ecological functions. Despite mesofauna having the potential to be used as indicators of soil quality, they are not frequently included in soil quality analysis. This study aimed to assess soil mesofauna's behavior and physico-chemical parameters under various land uses to better understand its effectiveness as a soil quality indicator. Soil samples were collected from 5 land-use types: Grazed Forest (F1), Ungrazed Forest (F2), Residential Area (Re), Upland Agricultural Area (UA), and Lowland Agricultural Area (LA) of Manthali Municipality, Nepal. For mesofauna, soil samples were collected using a quadrat along with the Berlese-Tullgren Funnel method for extraction and literature for identification. A total of 601 soil mesofauna were recorded, belonging to 8 classes. Oribatida and Collembola were the most abundant taxa, found in almost all land-use types, while few were specific to a particular land-use type. Shannon Wiener Diversity Index ranged from 0.82 (Re) to 1.22 (F1). Notably, Re showed high mesofaunal abundance but low diversity, highlighting an abundance-diversity trade-off under urban stress. The mesofaunal diversity was found to be influenced by soil moisture content, soil pH, temperature, and soil organic matter content. Among almost all soil parameters assessed, UA was superior to other land-use types, while Re had poor soil quality with the least mesofaunal diversity. In addition, Re had a high abundance of highly tolerant taxa like Oribatida and Collembola, indicating high stress in this land-use type. Moreover, the abundant number of mesofauna and the presence of Araneae in F2 possibly indicated healthy soil, as they play an important role in the soil food chain as predators. Thus, these findings provide important insights for incorporating soil mesofauna and other physico-chemical parameters to indicate soil quality.